Isolation of Lactic Acid Bacteria from Soil and Its Antifungal Activity Against Aspergillus flavus - Athiyyah Jihan Tifani; Tjahjadi Purwoko; Ari Susilowati (Pusat Penelitian dan Pengembangan Bioteknologi dan Biodiversitas (P3BB) LPPM UNS, 2025)
Food stocks, such as grains, fruits, and vegetables are vulnerable to spoilage by Aspergillus flavus, which typically controlled using chemical preservatives. Concerns about the health impact of these chemicals highlight the need for safer alternatives, such as biopreservatives. Lactic acid bacteria (LAB) are Generally Recognized as Safe (GRAS) microorganisms and have potential application as biopreservative agent, because LAB produced various metabolites with antifungal activities. LAB could be found in nutrient-rich environments, including rhizosphere soil and poultry house soil due to the nutrient residues for growth. The aims of this study were to isolate LAB from soils and to evaluate their antifungal activity with a focus on potential applications as biopreservatives. The LAB isolates from soil were characterized and screened for antifungal activity using the dual culture method. The LAB isolates inhibited A. flavus growth with the largest growth inhibition was showed by LAB isolate 1 that isolated from poultry house soil (17.65%). However, statistics analysis showed that fungal growth inhibition by LAB isolates were not significantly difference (p>0,05). Although the result was not statistically significant, all LAB isolates significantly inhibited conidia development. This showed potential application of LAB isolates as biopreservative agent. Keywords: antifungal, Aspergillus flavus, biopreservative, food stock, lactic acid bacteria